Degenerative relationships in lumbar intervertebral discs and facet joints: an MRI-based comparative study of asymptomatic individuals and patients with chronic and intermittent low back pain - Schmidt, Hendrik; Reitmaier, Sandra; Yang, Daishui; Duda, Georg; Pumberger, Matthias (Frontiers in Bioengineering and Biotechnology, 2025)
Degeneration of intervertebral discs and facet joints are common conditions that are thought to be interrelated. This study aimed to investigate the morphological interplay between disc and facet degeneration, as well as relationships between adjacent discs and facets. This prospective study involved 712 participants (307 males, 405 females) categorized into three groups: no back pain (no-BP), intermittent (iLBP), and chronic low back pain (cLBP). The Pfirrmann classification was used to assess intervertebral disc degeneration of index and adjacent segments, while the Fujiwara classification evaluated facet joint degeneration. Spearman’s correlation coefficient analyzed relationships between degenerative changes in discs and facets. Overall, from the 712 participants 254 were with no-BP, 159 with intermittent LBP, and 299 with chronic LBP. The severity of both intervertebral disc and facet joint degeneration in the MRI sequences increased from upper to lower segments, with a significant clear directionality in differences between the uppermost and lowermost levels (p < 0.01). A strong positive correlation was observed between degenerative changes of adjacent intervertebral discs, especially in the upper and middle lumbar spine (ρ > 0.69). However, correlations between intervertebral disc and facet joint degeneration were weak in all populations studied (ρ < 0.31). The data indicate a directionality in the disease progression, with a strong correlation observed between adjacent intervertebral discs, suggesting a concurrent degenerative process. In contrast, the weak correlations between disc and facet joint degeneration imply that these structures undergo independent degenerative processes, particularly in the early stages of degeneration. Further research is essential to elucidate the underlying mechanisms and to develop precise therapeutic interventions for lumbar spine degeneration.